2022
DOI: 10.1007/s13540-022-00044-0
|View full text |Cite
|
Sign up to set email alerts
|

Fractional Euler numbers and generalized proportional fractional logistic differential equation

Abstract: We solve a logistic differential equation for generalized proportional Caputo fractional derivative. The solution is found as a fractional power series. The coefficients of that power series are related to the Euler polynomials and Euler numbers as well as to the sequence of Euler’s fractional numbers recently introduced. Some numerical approximations are presented to show the good approximations obtained by truncating the fractional power series. This generalizes previous cases including the Caputo fractional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Put x = a and using Equation (9) in Equation ( 8), we get D 𝑗,𝜓 𝜙(a) = c 𝑗 Γ(𝑗 + 1), which gives, c 𝑗 = D 𝑗,𝜓 𝜙(a) Γ(𝑗+1) . Thus, 𝜓-Taylor polynomial with respect to a function is…”
Section: Generalized Fractional Taylor Theoremmentioning
confidence: 99%
See 1 more Smart Citation
“…Put x = a and using Equation (9) in Equation ( 8), we get D 𝑗,𝜓 𝜙(a) = c 𝑗 Γ(𝑗 + 1), which gives, c 𝑗 = D 𝑗,𝜓 𝜙(a) Γ(𝑗+1) . Thus, 𝜓-Taylor polynomial with respect to a function is…”
Section: Generalized Fractional Taylor Theoremmentioning
confidence: 99%
“…For the existence and uniqueness of the mild solution of the fractional integro‐differential with the nonlocal initial condition described by the Caputo fractional operator, we refer the reader to Sene 8 and references therein. Nieto 9 solved a logistic differential equation for generalized proportional Caputo fractional derivative.…”
Section: Introductionmentioning
confidence: 99%
“…15 Numerous mathematicians and physicists contributed to the improvement of the hypotheses of fragmentary calculus. [16][17][18][19] Fractional calculus has been studied by a significant number of scientists and others,. [20][21][22] Recent experiments in the physical sciences and engineering have shown that a wide range of nonclassical phenomena can be modeled by calculus fractional derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous mathematicians and physicists contributed to the improvement of the hypotheses of fragmentary calculus 16–19 . Fractional calculus has been studied by a significant number of scientists and others, 20–22 .…”
Section: Introductionmentioning
confidence: 99%
“…The logistic differential equation has many applications in different fields. Recently, the fractional version of the logistic equation has been considered by several authors [5,6,[9][10][11][12][13]. Power series representation of the solution of the fractional logistic equation and the existence of solution is discussed in Area and Nieto [10].…”
Section: Introductionmentioning
confidence: 99%